2006
DOI: 10.1117/1.2177650
|View full text |Cite
|
Sign up to set email alerts
|

Automatic inspection of pavement cracking distress

Abstract: This paper presents the image-processing algorithm customized for high-speed, real-time inspection of pavement cracking. In the algorithm, a pavement image is divided into grid cells of 8 x 8 pixels, and each cell is classified as a non-crack or crack cell using the grayscale information of the border pixels. Whether a crack cell can be regarded as a basic element (or seed) depends on its contrast to the neighboring cells. A number of crack seeds can be called a crack cluster if they fall on a linear string. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(77 citation statements)
references
References 2 publications
0
76
0
1
Order By: Relevance
“…[5], Huang and Xu [12], Li et al [18], Moussa and Hussain [20], Oliveira and Correia [23], Salman et al [31], Subirats et al [34], Tanaka and Uematsu [35],Varadharajan et al [38], Vivekanandreddy et al [39], Zou et al [43]). However, all of the methods mentioned above consider only one type of distress.…”
Section: State Of Research and Practice In The Pavement Distress Detementioning
confidence: 99%
“…[5], Huang and Xu [12], Li et al [18], Moussa and Hussain [20], Oliveira and Correia [23], Salman et al [31], Subirats et al [34], Tanaka and Uematsu [35],Varadharajan et al [38], Vivekanandreddy et al [39], Zou et al [43]). However, all of the methods mentioned above consider only one type of distress.…”
Section: State Of Research and Practice In The Pavement Distress Detementioning
confidence: 99%
“…The post processing of the images is done by AIES 6 (Monti 1995;Gavilán et al 2011) The Texas Department of Transportation developed the vehicle for data collection with the software, Vcarck. The vehicle is equipped with line scanning camera and the system for crack detection that can work at 112.5 km per sec (Huang & Xu 2006;Xu 2006). TRL in 2011 found that the ratio of true-negative crack detection is a bit high in ARAN and TRL system and Waylink systems.…”
Section: Automated Data Collection Vehiclesmentioning
confidence: 99%
“…Data for the vertical direction of crack progressing direction was obtained with sub-pixel accuracy by using Bspine interpolation (2). B-spline function is robust to against gaussian noise being distributed around crack [5].…”
Section: ) Crack Data Acquisitionmentioning
confidence: 99%